Проблемы повышения доходной части бюджета муниципального образования - Fateeva S. V., Podorin S. A. (Relevant lines of scientific research: theory and practice, 2016)
The article is devoted to the formation and increase of budget revenues of the municipality. The object of the acts of article II of the St George district of the Stavropol territory. In the article the directions of solving this problem through the introduction of a unique tax levied only on the territory of this municipal formation
Keywords: налоги; бюджет; муниципальное образование; taxes; budget; доходы местного бюджета; эксклюзивный налог; Municipal education; local budget revenues; exclusive of tax